Electrophysiological Characteristics of Fetal Atrioventricular Block - Zhao, Hui (2008)
OBJECTIVES: The purpose of our work was to define the complex electrophysiological characteristics seen in second- (2°) and third-degree (3°) atrioventricular block (AVB) and to longitudinally follow the development of atrial and ventricular heart rate and rhythm patterns with a goal of identifying heart rate and rhythm patterns associated with urgent delivery or neonatal pacing. BACKGROUND: The electrophysiological characteristics of congenital AVB before birth have not been extensively studied, yet the mortality from this disease is substantial. Along with advances in fetal therapies and interventions, a comprehensive natural history specific to the etiology of AVB, as well as the electrophysiological factors influencing outcome, are needed to best select treatment options. METHODS: Twenty-eight fetuses with AVB were evaluated by fetal magnetocardiography; 21 fetuses were evaluated serially. RESULTS: Fetuses with 2° AVB and isolated 3° AVB showed: 1) diverse atrial rhythms and mechanisms of atrioventricular conduction during 2° AVB; 2) junctional ectopic tachycardia and ventricular tachycardia during 3° AVB; 3) reactive ventricular and atrial fetal heart rate (FHR) tracings at ventricular rates >56 beats/min; and 4) flat ventricular FHR tracings at ventricular rates <56 beats/min despite reactive atrial FHR tracings. In contrast, fetuses with 3° AVB associated with structural cardiac disease exhibited predominantly nonreactive heart rate tracings and simpler rhythms. CONCLUSIONS: Second-degree AVB, isolated 3° AVB, and 3° AVB associated with structural cardiac disease manifest distinctly different electrophysiological characteristics and outcome. Fetuses with 2° AVB or isolated 3° AVB commonly exhibited complex, changing heart rate and rhythm patterns; all 19 delivered fetuses are alive and healthy. Fetuses with structural cardiac disease and 3° AVB exhibited largely monotonous heart rate and rhythm patterns and poor prognosis. Junctional ectopic tachycardia and/or ventricular tachycardia may be characteristic of an acute stage of heart block.